Youth on trial: How framing and language influence public support for harsh sentences - Hansen, Michael A; Navarro, John C (Oxford University Press (OUP), 2026)
We investigated how question wording and framing influence public attitudes towards sentencing juvenile murder offenders. Using an experimental survey of 1,193 U.S. adults, we test the effects of three terms or frames: “individual under the age of 18,” “child,” and a neuroscientific prompt describing adolescent brain development, emphasizing delayed maturation of the prefrontal cortex. The term “child” reduces support for harsher sentences, including adult sentencing, life imprisonment, and the death penalty, while increasing support for a 15-year maximum sentence. The neuroscientific prompt had minimal effect on attitudes towards harsh sentences, suggesting that the “child” term is more effective than technical explanations. Gender moderated framing effects, with the child framing having stronger impacts on men than on women.